A new species of Eleodes (Eleodes) from Mexico, with ecological and phenological notes (Coleoptera: Tenebrionidae) - Triplehorn, Charles A.; Ruiz, Paulina Cifuentes (Zootaxa, 2011)
The genus Eleodes is the largest among the Tenebrionidae of North America, with more than 200 known species. Some are widespread, ranging from Canada to Mexico while others have a more restricted distribution. The larvae of the species, known as false wireworms are very damaging to crops in irrigated farmland. The following new species is a surprising addition to the Mexican beetle fauna, especially since it was discovered in an area where much fieldwork has been done over the years.